New aspects of the environmental risks of quantum dots: prophage activation. Issue 7 (11th June 2018) - Xu, Juan; He, Huan; Wang, Ying-Ying; Yan, Ren; Zhou, Lian-Jiao; Liu, Yu-zhu; Jiang, Feng-Lei; Maskow, Thomas; Liu, Yi
Abstract : CdTe QDs induce lysogenic bacteria into the lytic cycle by damaging the DNA. Abstract : A few thousand tons of nanoparticles and quantum dots (QDs) are produced yearly worldwide, and a significant amount is released into ecosystems. This knowledge has stimulated numerous studies on the toxicological properties of these nanomaterials. However, an important ecotoxicological aspect has been largely overlooked: the activation of silent viruses in bacteria (the so-called prophages). This is particularly important because, once the prophages are activated, phage replication using bacterial hosts is an autocatalytic process with a potentially exponential rate of bacteria killing under certain conditions. To shed light on these underestimated processes, the interactions of differently functionalized CdTe QDs with E. coli containing lambda prophages were investigated. We found that prophages can be activated with as little as a nanomolar concentration range of QDs. DNA damage due to oxidative stress induced by the CdTe QDs was revealed as the main reason for the prophage activation. The contribution of freely dissociated Cd 2+ to prophage activation was on the order of 15 to 25%. Our pioneering work is intended to provide the first examination to better understand the role of nanoparticles in aquatic ecosystems.